2018
DOI: 10.1039/c7en01046j
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of air discharge-generated manganese oxide nanoparticles: comparison to welding fumes

Abstract: Exposures to high doses of manganese (Mn) via inhalation, dermal contact or direct consumption can cause adverse health effects. Welding fumes are a major source of manganese containing nanoparticles in occupational settings. Understanding the physicochemical properties of manganese-containing nanoparticles can be a first step in understanding their toxic potential following exposure. In particular, here we compare the size, morphology and Mn oxidation states of Mn oxide nanoparticles generated in the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
(58 reference statements)
2
14
0
Order By: Relevance
“…Previously, the generation of Fe and Mn nanoparticles was simulated to have a close model to characterize the materials and their behavior under contact with biological solutions. (65,68) However, from this study, it is concluded that new models that include heterogeneous agglomerates of incidental nanoparticles (Fe-Mn-Cu and Fe-Mn-Zn) with both architectures are required to better understand the health implications that these incidental nanoparticles will have.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, the generation of Fe and Mn nanoparticles was simulated to have a close model to characterize the materials and their behavior under contact with biological solutions. (65,68) However, from this study, it is concluded that new models that include heterogeneous agglomerates of incidental nanoparticles (Fe-Mn-Cu and Fe-Mn-Zn) with both architectures are required to better understand the health implications that these incidental nanoparticles will have.…”
Section: Discussionmentioning
confidence: 98%
“…(40) This can have a significant effect on the inflammatory responses that the agglomerates will generate in the lung as each oxide dissolves at different rates. (64,65) In addition, the transport of the same INPs to different parts of the respiratory tract may generate different health effects. (66) For example, ZnO and Cu/CuO nanoparticles have shown to dissolve in the lung mostly by macrophage action, (64,67) but there is no indication that dissolution will occur if transported directly to the brain by the olfactory system.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have experimentally showed that metals and heavy metals emitted by welding fumes still pollute the environment. • Therefore, it can be clearly stated that these materials are vented into the atmosphere and threaten the environment and human health because the fume produced during the welding process contains many different oxides and elements (Stockmann-Juvala et al, 2013;Stebounova et al, 2018;McCarrick, et al, 2019). • The data obtained in this study provide important information for understanding the effects of welding fumes on health and environment.…”
Section: Discussionmentioning
confidence: 84%
“…Since welding fumes consist of ultra-fine particles, these structures were essentially shapeless. The structures of the phases obtained from the XRD analysis given in Table 1 were composed of different crystal lattice structures as reported in previous studies (Ehrman et al, 1999;Stebounova et al, 2018). During the condensation of these particles, separate molecules may get together to form different phases in a single structure.…”
Section: Characterization By Xrdmentioning
confidence: 87%
See 1 more Smart Citation